Contribution Of Strategies To Sustainable Competitive Advantage Among Banks After Interest Rate Controls Reintroduction In Kenya - Okeyo, Washington; Irene, Luvisia Doris (Advances in Social Sciences Research Journal, 2017)
High competition in the banking sector forces banks to adopt appropriate strategies for competitive advantage. This study examined contribution of competitive strategies to sustainable competitive advantage in the sector. The study used a cross sectional design on a target population of all the 43 banks in Kenya. The sample for the study however concentrated in Nairobi County which had 38 banks and a total workforce of 3770. Respondents were proportionately stratified by employee category to arrive at total number of 377. Primary data was collected from 377 respondents using structured questionnaires through drop and pick method. Secondary data was collected through desk and content analysis from the bank’s records and reports. Statistical Package for Social Sciences V 22.0 was used to analyze data. Descriptive, inferential, correlation, and regression methods were used to analyze data. Resulting central tendency measures and correlation and regression coefficients were used to establish the relationship between competitive strategies and sustainable competitive advantage. The study findings indicate that differentiation strategy and sustainable competitive advantage are positively and significantly related (r=0.166, p=0.001) and cost leadership strategy and sustainable competitive advantage are positively and significantly related (r=0.085, p=0.034). This study thus concludes that cost leadership strategy and differentiation strategy have an impact on competitive advantage and should be pursued banks. Banks should adopt differentiation strategy and cost leadership strategy in the wake of interest rates reintroduction.